Neuroinflammation as the Underlying Mechanism of Postoperative Cognitive Dysfunction and Therapeutic Strategies - Li, Zhichao; Zhu, Youzhuang; Kang, Yihan; Qin, Shangyuan; Chai, Jun (Frontiers in Cellular Neuroscience, 2022)
Postoperative cognitive dysfunction (POCD) is a common complication following surgery/general anesthesia, especially in elderly patients. Severe cases will greatly delay patient discharge, affect the patient’s quality of life after surgery, and even pose a heavy burden to society. In addition, as the population ages, surgery is increasingly being used for progressively elderly patients and those with higher prevalence of complications. And this trend brings a huge challenge to the current healthcare system. Although study on POCD is in full swing, its underlying pathogenesis remains unclear due to conflicting results and debatable evidence. According to existing studies, its occurrence and development are related to multiple factors. Among them, the pathogenesis of neuroinflammation in POCD has become a research hotspot in recent years, and a great deal of clinical as well as preclinical studies have gradually confirmed the correlation between neuroinflammation and POCD. In this paper, we reviewed how central nervous system inflammation occurs and develops as well as how it leads to the evolution of POCD, concerning the changes of peripheral circulation, pathological pathways between peripheral circulation and central nervous system (CNS). Furthermore, we proposed some potential therapeutic targets, diagnosis and treatment strategies at the cellular and molecular levels, and clinical applications. Accordingly, this paper will provide a better perspective for us to understand the occurrence, development and preventive strategies of POCD, which is conductive to help us be equipped to manage these vulnerable geriatric patients.